Healthy ageing in the far North: perspectives and prescriptions. Issue 1 (1st January 2020) - Peterson, Jennifer R.; Baumgartner, Didar A.; Austin, Sabrina L.
ABSTRACT: Objectives : This study captured factors integral to healthy ageing in central Alaska. To date, conceptual models fail to meaningfully address how healthy ageing is impacted by location and context, particularly in remote or sparsely populated areas. The way "healthy", or "successful", ageing is defined in an extreme environment, and how that contrasts with global definitions of healthy ageing, has yet to be examined. Method : Residents of central Alaska aged 60 and older completed background demographics and several measures of personality and well-being and then engaged in a guided discussion. Results : Themes identified as important to healthy ageing were attitude/perspective, socialisation, sense of community, purpose and staying active, and independence. Challenges endorsed included service gaps, transportation, seasonality, cost of living, and isolation. Discussion : The current data parallels previous investigations of healthy ageing and provides a new understanding of the importance of resilience factors for those living in central Alaska.